Globalisation and COVID-19 - Chatterji, Manas; Luterbacher, Urs; Fert, Valérie; Chen, Bo (Contributions to conflict management, peace economics and development ;, 2023)
The beginnings of globalisation are usually dated to the last third of the twentieth century, alongside the rise of supranational companies, the financial economy and the information technology revolution. However, from the time the Earth was "anthropocized" during the Palaeolithic era, globalisation has not ceased, though it has seen a number of fluctuations, including the era of WWI and during the COVID-19 pandemic. Globalisation and COVID-19 examines how the simultaneous immobilisation of billions created a temporary hold on the mobility which constitutes the very irrigation of globalisation. In this 31st volume of the book series Contributions to Conflict Management, Peace Economics and Development, world-renowned contributors explore the pandemic through the lens of globalisation, analysing its implications for the globalised world and its development over time. Through innovative tools and methodologies of emerging social sciences like Regional Science, Peace Science, and particularly of Management Science which includes artificial intelligence and quantum mechanics, Globalisation and COVID-19 brings together researchers and practitioners to create a transversal and systemic approach necessary to interrogating essential questions of pandemic-era globality.